Digital Literacy and Social Media in Shaping Political Democracy in the Digital Era - Binti Latifah; Nasywa Haniya Nurbani; Rachmat Pirdaus; La Viola Prasasti; Khoiriya Ulfah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The development of digital technology has transformed the practice of political democracy by creating a more open space for participation through social media. This study aims to analyze the role of digital literacy as an internal factor and social media exposure as an external factor in shaping political democracy in the digital age. The method used was a Systematic Literature Review (SLR) of 15 relevant scientific articles. The results of the study indicate that digital literacy plays a crucial role in enhancing individuals’ ability to critically understand and filter political information, while social media exerts a dual influence: serving as a means to boost political participation while simultaneously acting as a source of disinformation. The interaction between the two is a key factor in determining the quality of political democracy. Therefore, improving digital literacy and the wise use of social media are essential steps in fostering a higher-quality democracy in the digital age.